2004
DOI: 10.1080/14992020400050049
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial work environment, hearing impairment and health

Abstract: This article summarizes results from a study of hearing-impaired men and women in the labour force in Sweden. A questionnaire about psychosocial work environment (in accordance with the Demand-Control Model), health and wellbeing was sent out and answered by 445 hearing-impaired people, 20-64 years of age. A large reference group had previously answered the same questionnaire. The results indicate that imbalances between demand and control (i.e. high demand and low control, so-called high stress work type) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
77
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 7 publications
9
77
1
Order By: Relevance
“…The present study focuses on adult patient perspective on functioning and disability in hearing loss and it part of the ICF Cores sets for Hearing loss project (Danermark et al, 2010 Kramer et al, 2005;Kricos & Holmes, 1996;Kricos et al, 1992) and participation in work (Danermark & Coniavitis Gellerstedt, 2004;Kramer, 2008). The results of the present study further emphasize the importance of investigating external influences, such as environmental factors, when assessing functioning of persons with HL.…”
Section: Discussionmentioning
confidence: 82%
“…The present study focuses on adult patient perspective on functioning and disability in hearing loss and it part of the ICF Cores sets for Hearing loss project (Danermark et al, 2010 Kramer et al, 2005;Kricos & Holmes, 1996;Kricos et al, 1992) and participation in work (Danermark & Coniavitis Gellerstedt, 2004;Kramer, 2008). The results of the present study further emphasize the importance of investigating external influences, such as environmental factors, when assessing functioning of persons with HL.…”
Section: Discussionmentioning
confidence: 82%
“…This is not surprising because people with hearing loss are established as a vulnerable group in the labour market with overrepresentation in early retirement (Danermark & Coniavitis Gellerstedt, 2004), increased emotional distress due to misinterpretation of external information at work (Morata et al, 2005) and experiencing lack of control in the work environment (Kramer et al, 2006). Threatening of the social bonds, as can occur when the interaction is interrupt by a hearing loss, may generate negative emotions (Scheff, 1990).…”
Section: Several Categories Also Belonged To Chapter 8 Major Life Armentioning
confidence: 99%
“…Activity/sickness compensation is almost three times higher for the population with total hearing loss than the reference population (Rydberg, Gellerstedt et al 2010). One study, based on selfreported psychosocial work environment in a group of hearing-impaired people in Sweden, found that hearing-impaired people with highly stressful work reported poorer physical health status and lower psychological well-being than normal-hearing peers (Danermark and Gellerstedt 2004 …”
Section: Hearing Disordersmentioning
confidence: 99%